Customer success how innovative companies are reducing churn and growing recurring revenue - Mehta, Nick 1977-; Steinman, Dan 1958- (Wiley, 2016)
"Your business success is now forever linked to the success of your customers Customer Success is the groundbreaking guide to the exciting new model of customer management. Business relationships are fundamentally changing. In the world B.C. (Before Cloud), companies could focus totally on sales and marketing because customers were often 'stuck' after purchasing. Therefore, all of the 'post-sale' experience was a cost center in most companies. In the world A.B. (After Benioff), with granular per-year, per-month or per-use pricing models, cloud deployments and many competitive options, customers now have the power. As such, B2B vendors must deliver success for their clients to achieve success for their own businesses. Customer success teams are being created in companies to quarterback the customer lifecycle and drive adoption, renewals, up-sell and advocacy. The Customer Success philosophy is invading the boardroom and impacting the way CEOs think about their business. Today, Customer Success is the hottest B2B movement since the advent of the subscription business model, and this book is the one-of-a-kind guide that shows you how to make it work in your company. From the initial planning stages through execution, you'll have expert guidance to help you: Understand the context that led to the start of the Customer Success movement Build a Customer Success strategy proven by the most competitive companies in the world Implement an action plan for structuring the Customer Success organization, teiring your customers, and developing the right cross-functional playbooks Customers want products that help them achieve their own business outcomes. By enabling your customers to realize value in your products, you're protecting recurring revenue and creating a customer for life. Customer Success shows you how to kick start your customer-centric revolution, and make it stick for the long term"--
Includes index. - Print version record and CIP data provided by publisher
Keywords: Customer relations; Customer services; Success in business; Service à la clientèle; Succès dans les affaires; BUSINESS & ECONOMICS; Customer Relations